2017
DOI: 10.1007/s00192-017-3495-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and randomized clinical trial comparing transobturator versus retropubic sling in terms of efficacy and safety

Abstract: The cure rates of the per-protocol analysis showed the noninferiority of the TOT relative to the RP sling. The RP sling group exhibited higher urinary retention. Quality of life improved significantly in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Veit-Rubin et al [10] detected POP in 25% of the patients that underwent BC. In contrast, PVS, MUSS and also the method used in the present study have no risk of POP formation as they do not require pelvic dissection which distorts urethral support during surgery, as in BC [28,29].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Veit-Rubin et al [10] detected POP in 25% of the patients that underwent BC. In contrast, PVS, MUSS and also the method used in the present study have no risk of POP formation as they do not require pelvic dissection which distorts urethral support during surgery, as in BC [28,29].…”
Section: Discussionmentioning
confidence: 88%
“…Ford et al reported the objective cure rates at the first and fifth postoperative years as 85% and 82% for TOT and as 87% and 85% for RT, respectively [19]. Palos et al reported that the objective cure rates of TOT and RT were 100% and 92% at postoperative month 12, respectively [22]. In SISTer trial, Albo et al [21] reported the objective cure rates for PVS and BC at the second year as 66% and 49%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations